Dimensions of politics and English jurisprudence / Sean Coyle. - Coyle, Sean (Cambridge University Press, 2013)
Understandings of law and politics are intrinsically bound up with broader visions of the human condition. Sean Coyle argues for a renewed engagement with the juridical and political philosophies of the Western intellectual tradition, and takes up questions pondered by Aristotle, Plato, Augustine, Aquinas and Hobbes in seeking a deeper understanding of law, politics, freedom, justice and order. Criticising modern theories for their failure to engage with fundamental questions, he explores the profound connections between justice and order and raises the neglected question of whether human beings in all their imperfection can ever achieve truly just order in this life. Above all, he confronts the question of whether the open society is the natural home of liberals who have given up faith in human progress (there are no ideal societies), or whether liberal political order is itself the ideal society?